Lessons from an intervention study on the sustainability of after-school comprehensive sexuality education in Zambia: the perspectives of teachers, health workers and guardians - Joar Svanemyr; Joseph Mumba Zulu; Ecloss Munsaka; Ingvild Fossgard Sandøy (Reproductive Health, 2024)
Abstract Background Comprehensive sexuality education (CSE) has been introduced in many sub-Saharan African countries, but limited political interest and insufficient funding have resulted in many CSE initiatives being dependent on donor funding or non-governmental organisations (NGOs) supporting its implementation. This has created concerns about the sustainability of the programmes. The objective of this study was to explore factors affecting the sustainability of CSE delivered through a youth club organized after school hours in Zambia. Methods We interviewed teachers and community health workers (CHWs) who had implemented CSE as part of an after-school youth club set up as part of a cluster randomized controlled trial. The trial evaluated the effectiveness of economic support for adolescent girls, CSE and community dialogue meetings on adolescent childbearing. Teachers and CHWs in 63 schools were trained to facilitate the CSE youth clubs, and they were given economic incentives during the trial´s two-year intervention period to organize meetings every fortnight. Two years after the external support for the youth clubs ended, we conducted qualitative interviews with the facilitators in 15 of the 63 schools, interviews with some head teachers, and focus group discussions with guardians of adolescent girls. Results Whereas CHWs were generally supportive of teaching adolescents about contraception, some of the teachers stressed that abstinence was the most effective method to avoid pregnancy and diseases. The respondents’ diverging points of view did not affect their willingness to continue teaching CSE, including contraception. However, the youth club meetings were only continued in a few schools after the external support period ended. This was attributed to transfers of trained teachers and a lack of training among the remaining staff; lapse of moral support, resources and incentives; limited involvement of the school management in the CSE initiative; and attention shifting to other projects. Conclusion To ensure the sustainability of CSE initiatives for adolescents, emphasis should be placed on training several teachers in each school, and continued moral support and encouragement also appeared essential. Trial registration: ISRCTN (ISRCTN12727868).